Implementation of Satintelkam Guna Early Detection Mapping of the 2024 Election Potential Vulnerability Index in Order to Realize Kamtibmas in the Police Malang - Fachrurozi, Andreas Silaban (Advances in Police Science Research Journal, 2024)
Election is an electoral process to elect most or all members of an elected body, legislative body, and president directly elected by the public. This election involves all Indonesian people in its implementation and this moment is also a means to exchange opinions, information, argue and most importantly donate through the fulfillment of people’s rights as voters / constituents. The writing of this final project script aims to analyze the implementation of Satintelkam early detection carried out by the Malang Regional Police, in order to map the Election Vulnerability Potential Index in order to realize Kamtibmas at the Malang Regional Police. In writing this final project, the author found findings in the form of the implementation of the Election Vulnerability Index (IPKP) policy that has not been optimal and faktors in the implementation of early detection that affect the results of the IPKP. IPKP in realizing Kamtibmas at the Malang Police Station is not enough to be pursued through early detection but needs other efforts such as law enforcement and fulfillment of accommodation for constituents on the way. From the results of the above research, it can be concluded that problem-solving steps are needed related to the author’s findings. Therefore, the author suggests building a narrative for regulations related to the fulfillment of policy support in the form of the number of personnel and allowances for personnel. In addition, the expansion of authority for Satintelkam members who can take action independently if they find violations in the main field during the pre-campaign, campaign period, and post-campaign which incidentally is the time when the most violations occur.